A Critique of the "Criminal Policy in Islam and in the Islamic Republic of Iran" - Naser Ghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Basically, each discipline is selected and chosen to indicate the content of the field, on the one hand, and it can explain its scope, such as sociology, rhetoric, criminology, and so on, on the other hand. While a criminal policy is a discipline that extends far beyond its title and includes many different subjects, it is also capable of evaluating from a diverse range of scientific disciplines, as well as various legal systems, especially religious and Islamic.About the concept of criminal policy from the past, the views of many writers in Western and Eastern societies, as well as in Iran before and after the Islamic Revolution, have been expressed, which in some cases require careful consideration. Addressing the secular and religious viewpoint of the criminal policy and plotting its place in these two groups: the first group is a subject that has been considered in the book of evaluation, and the author has attempted to explain the position and its role in religious matters, and consequently it is in the current legal system of the Islamic Republic of Iran.